New Distribution Record of Tetrigona apicalis (Smith, 1857) (Hymenoptera: Apidae: Meliponini) in Ujung Kulon National Park, Indonesia - Miharja, Jajang; Atmowidi, Tri; Priawandiputra, Windra; Perwitasari, Dyah; Kahono, Sih (Bogor Agricultural University, Indonesia, 2026)
Ujung Kulon National Park (UKNP) is located in the western part of Java Island, Indonesia. This national park was designated a Natural World Heritage Site by UNESCO in 1992. The stingless bee species, Tetrigona apicalis (Apidae: Meliponini), has not previously been documented in specific locations on Java Island. In this study, we found a new distribution record of T. apicalis in UKNP. Here, we described of its nest-entrance characteristics, morphological features, and morphometry. The colony of bee species was found in the forest of Mount Honje, UKNP, Indonesia, at an altitude of 883 m asl. The nest is located in a Tiliaceae tree cavity at a height of 420 cm from the ground surface. The shape of the nest entrance of the bee species was irregular, with a longitudinal diameter of 3.2 cm and a vertical diameter of 5.7 cm, and it had a light brown color. Locally, this bee is known as teuwel meunyan, referring to a traditional incense burner due to the aromatic scent associated with its use in religious rituals. The findings contribute to the current knowledge of the distribution of T. apicalis on Java Island, particularly within UKNP, and provide data for future conservation and sustainable utilization efforts.